A Comparativistic Analysis of the Transformation of Alimentary Aspect of the Other’s Image: 2018-2022 - Rastyam T. Aliev; Olesya S. Yakushenkova (Журнал Фронтирных Исследований, 2022)
The study focuses on the transformation of the alimentary models of the imaginative Other. Based on the statistics of the Russian Internet queries, the authors identified a number of markers, determining the main alimentary models of the Other. They carried out a comparative analysis of the obtained in 2018-2019 (pre-Сovid-19) models with similar Post-Covid models for 2021-2022. The researchers' hypothesis is that the queries can reveal the attitude of the modern Russians to the Other, determine the criteria by which the images are formed and the factors, affecting their transformation.